Multicarrier Waveform Candidates for Beyond 5G - khan, Bahram (2020)
To fulfil the requirements of 5G vision of “everything everywhere and always connected”, a new waveform must contain the features to support a greater number of users on high data rate. Although Orthogonal Frequency Division Multiplexing (OFDM) has been widely used in the 4th generation, but it can hardly meet the needs of 5G vision. However, many waveforms have been proposed to cope with new challenges. In this paper, we have presented a comparative analysis of several waveform candidates (FBMC, GFDM, UFMC, F-OFDM) on the basis of complexity, hardware design and other valuable characteristics. Filter based waveforms have much better Out of Band Emission (OoBE) as compared to OFDM. However, F-OFDM has smaller filter length compared to filter-based waveforms and provides better transmission with multiple antenna system without any extra processing, while providing flexible frequency multiplexing, shorter latency and relaxed synchronization as compared to other waveforms.